Incidence, mortality and survival trends of penile cancer in Lithuania 1998–2017 - Drevinskaite, Mingaile; Patasius, Ausvydas; Kincius, Marius; Jonušas, Justinas; Ladukas, Adomas; Jievaltas, Mindaugas; Kairevice, Laura; Smailyte, Giedre (Frontiers in Oncology, 2023)
Background and objectives: The aim of this study was to analyse trends in penile cancer incidence, mortality, and relative survival in Lithuania during the period of 1998–2017. Materials and Methods: The study was based on all cases of penile cancer reported to the Lithuanian Cancer Registry between 1998 and 2017. Age-specific rates standardized rates were calculated, using the direct method (World standard population). The Joinpoint regression model was used to provide estimated average annual percentage change (AAPC). One-year and five-year relative survival estimates were calculated using period analysis. Relative survival was calculated as the ratio of the observed survival of cancer patients and the expected survival of the underlying general population. Results: During the study period, the age-standardized incidence rate of penile cancer varied between 0.72 and 1.64 per 100 000, with AAPC 0.9% (95% CI -0.8–2.7). The mortality rate of penile cancer in Lithuania during this period varied from 0.18 to 0.69 per 100 000, with AAPC of -2.6% (95% CI -5.3–0.3). Relative one-year survival of patients, diagnosed with penile cancer improved over the time from 75.84% in period 1998–2001 to 89.33% in period 2014–2017. Relative five-year survival rate of patients, diagnosed with penile cancer changed from 55.44% in period 1998-2001 to 72.90% in period 2014–2017. Conclusions: The incidence rates of penile cancer showed an increasing trend, while mortality rates were decreasing in Lithuania during 1998-2017. One-year and five-year relative survival increased, however, it does not reach the highest scores of Northern European countries.